2007
DOI: 10.1093/humrep/dem034
|View full text |Cite
|
Sign up to set email alerts
|

Levonorgestrel pharmacokinetics in plasma and milk of lactating women who take 1.5 mg for emergency contraception

Abstract: Nursing mothers may need EC. These results suggest that to limit infant exposure to the period of maximum LNG excretion in milk, mothers should discontinue nursing for at least 8 h, but not more than 24 h, after EC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 46 publications
1
21
0
1
Order By: Relevance
“…20,22 To minimize the infant's exposure to levonorgestrel, mothers should consider not nursing for at least 8 hours after ingestion, but no more than 24 hours is needed. 23 …”
Section: ■ Emergency Contraception and Breastfeedingmentioning
confidence: 99%
“…20,22 To minimize the infant's exposure to levonorgestrel, mothers should consider not nursing for at least 8 hours after ingestion, but no more than 24 hours is needed. 23 …”
Section: ■ Emergency Contraception and Breastfeedingmentioning
confidence: 99%
“…Recent evidence suggests that progestins in contraceptives can enter mother's milk, can be detected in the serum of breast-fed infants (2)(3)(4)15), and may influence the infant hypothalamo-pituitary-thyroid axis (16). Yet a recently published meta-analysis of clinical reports concluded that evidence regarding the use of hormonal contraceptive during lactation is limited and of poor quality and stressed the urgent need for a properly conducted clinical trial in this field (17).…”
Section: P Use In Humansmentioning
confidence: 99%
“…Preliminary studies from our laboratory demonstrate that plasma P levels in mothers and fetuses are positively correlated at the end of gestation and suggest that P from maternal circulation can bind to nuclear PR within the fetal male rat MPN (20). In humans, progesterone has been isolated and quantified in mother's milk (51), and it has been demonstrated that progestins in milk can pass to breast-fed neonates (2)(3)(4). In addition to potential maternal sources of P, the perinatal rodent brain expresses all the enzymes necessary for the de novo synthesis of P from cholesterol (52)(53)(54)(55), potentially producing locally high concentrations of P within specific brain regions.…”
Section: Possible Sources Of Endogenous P In Developing Male Brainmentioning
confidence: 99%
See 1 more Smart Citation
“…À noter que le Norlevo 1 est utilisable y compris en cas d'allaitement [26]. Toutefois, certains auteurs considèrent, à partir de données pharmacocinétiques, qu'il serait souhaitable de suspendre l'allaitement dans les huit heures suivant la prise du comprimé [27].…”
Section: En Suites De Couchesunclassified